CRISPR-Cas9 mediated editing of starch branching enzyme, SBE2 gene in potato for enhanced resistant starch for health benefits - Batta, Sudha; Siddappa, Sundaresha; Sharma, Neha; Singh, Rajender; Gupta, Reena; Kumar, Dinesh; Singh, Brajesh; Thakur, Ajay Kumar (Frontiers in Genome Editing, 2025)
Potato is an important vegetatively propagated, starch-rich tuber crop. High amylose potatoes containing more resistant starch offer healthier food alternatives. However, the resistant starch content is low in most cultivated potato varieties. In this study, targeted mutation of the starch branching enzyme2 (SBE2.1 & SBE2.2 isoforms) had been done in the commercially significant potato cultivar, Kufri Chipsona-I using Clustered regularly interspaced short palindromic repeats-CRISPR-associated protein 9 (CRISPR-Cas9 system) to develop high-amylose potato lines. SBE2 is one of the key enzymes involved in amylopectin biosynthesis, a starch component. Two isoforms, SBE2.1 & SBE2.2, were mutated using CRISPR-Cas9-mediated genome editing. After Agrobacterium-mediated genetic transformation, fifty transformed lines were generated on herbicide Basta selection medium, out of which 70% were found positive for bar and Cas9 genes. Overall, six mutant lines, viz. K301, K302, K303, K304, K305, K306, derived from distinct events, exhibited deletions and substitutions in the target exons. The CRISPR-Cas9 edited K304 potato line exhibited both insertion–deletion (indel) and substitution mutations in three out of the four selected targets across both genes, and was therefore identified as the most efficiently edited line. The harvested tubers from SBE2.1 & SBE2.2 mutant K304 line showed the highest amylose (95.91%) and resistant starch content (8.69 g/100 g). Evaluation of starch using X-ray crystallography (XRD) illustrated an altered crystallinity index (CI%) in all six mutant events in comparison to the wild study. Furthermore, 1H-NMR study demonstrated a substantial decline in branch chain elongation in amylopectin, and thus a low degree of branching in a range of 1.15%–3.66% was reported in mutant lines, relative to the wild type (5.46%). The present study demonstrated the efficacy of CRISPR-Cas9-mediated mutagenesis of starch biosynthetic genes to develop high-amylose potato lines with elevated resistant starch content for improved health benefits.